Substance use and social influence as risk factors for nicotine and tobacco product use in adolescents and young adults who use electronic nicotine delivery systems - Hatz, Laura E.; Courtney, Kelly E.; Wallace, Alexander L.; Wade, Natasha E.; Baca, Rachel; Doran, Neal; Jacobus, Joanna (Frontiers in Adolescent Medicine, 2025)
BackgroundNicotine and tobacco product (NTP) use in adolescence and young adulthood is associated with negative health and psychosocial outcomes. This study prospectively tested alcohol use, cannabis use, and peer and family NTP use as predictors of NTP use in adolescents and young adults (AYAs) who were NTP naïve or who primarily used electronic nicotine delivery systems (ENDS).MethodParticipants (N = 133) ages 16–22 completed a baseline laboratory visit and follow-up session 1 year later. Participants’ baseline alcohol use, cannabis use, and NTP use by peers and family were tested as risk factors for any and moderate to heavy (at least monthly) NTP use at follow-up. Logistic regressions were conducted for the full sample (N = 133) and in a subsample of participants reporting no to low NTP use at baseline (n = 76).ResultsBaseline alcohol use, cannabis use, and peer and family NTP use were associated with NTP use at 1-year follow-up, over and above baseline NTP use. Peer and family NTP use emerged as the most consistent predictor of AYA NTP use (ORs: 4.059–8.432), while recent cannabis and alcohol use exerted effects (ORs: 1.003–1.021) that varied by NTP use level.DiscussionA confluence of variables, including prior substance use and social and familial influences, act as risk factors for NTP use in AYAs who primarily use ENDS. Identification of risk and protective factors for NTP use is necessary to inform efforts to decrease NTP use in this developmentally vulnerable population.